BIAS GENDER DALAM KEGIATAN AGRIBISNIS HORTIKULTURA SAYURAN DI KABUPATEN JEMBER, PROPINSI JAWA TIMUR - M. Sunarsih (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2009)
Agribiness is one of agricultural activities that cover some subsistems for example form management subsisten many female and male labour in farm management subsisten, because the development of agricultural technology it means availability of female labour. The female labour opportuny will support many female labour to get income. Beside that the equality of human right between male and female labour. The research conducted in Panti and Umbulsri area especially farm management cabbage and string bean on July 2007. The porposes of this reseach are: (1.) to indentity female labour and to know the fenomenon on cabbage and string bean farm management, (2.) to know the wage and income of female labour on cabbage and string bean farm management, (3.) to know the income female labour contribution on cabbage and string bean fram management, (4.) to know the factors enfluence the income of female labour on cabbage and string bean farm management . So it means opportunity of female in labour market become wider. The determine research area used purposive sampling methode, research methode used discriptive comparative, data colleded primary and secondary. The sample methode used random sampling. The sample are farmers and female labour who work in cabbage and string bean farm management all of respondent are 80 people, 40 respondent as a farmer on cabbage and string bean and 40 respondent as female labour. Statistic analysis using tabulation propotion and multiple linier regression. The result of this research are: (1.) there is gender bias on vegetable horticultural agribisness activities cabbage farm management female labour 38,17% and male labour 61,83%, string bean farm management female labour 63,66% and male labour 36,34%, (2.) there is gender bias on female wages cabbage farm management female labour Rp 7.500,- /half day , male labour Rp10.000,- /half day, string bean farm management female labour Rp 7.000,-/half day, male labour Rp 10.000,-/half day, (3.) The income female labour contribution toward family income on cabbage farm management is 18,64%, string bean farm management 43,63%, (4.) Age, education, number of family influenced the income of female labour. Keyword: The Gender bias , Agribisness Activities